Examining the Impact of Capital Structure and Board Diversity on Firm Performance: Evidence from Pakistan Stock Exchange (Journal of Asian Development Studies, 2024)
This study aims to investigate the relationship between capital structure, board diversity, and firm performance among KSE-100 index firms listed on the Pakistan Stock Exchange. We use a panel data approach and STATA MP-14 to analyze the impact of two capital structure measures (debt-to-equity ratio and debt-to-total assets) and three board diversity measures (female representation, female executive presence, and male executive presence) on three financial performance indicators (firm size, firm age, and return on equity). Our findings reveal a significant positive association between debt financing and female board representation, as well as a positive relationship between capital structure and female executive presence. However, we find an insignificant and negative relationship between capital structure and managerial ownership. This study contributes to the existing literature on corporate governance and capital structure by highlighting the importance of board diversity in emerging markets. Future studies can build on our findings by exploring the relationship between capital structure and board diversity in other developing countries and comparing the results to identify potential variations.